Apart but Connected: Online Tutoring and Student Outcomes during the COVID-19 Pandemic - Michela Carlana; Eliana La Ferrara (Institute of Labor Economics (IZA), 2021)
In response to the COVID-19 outbreak, the governments of most countries ordered the closure of schools, potentially exacerbating existing learning gaps. This paper evaluates the effectiveness of an intervention implemented in Italian middle schools that provides free individual tutoring online to disadvantaged students during lock-down. Tutors are university students who volunteer for 3 to 6 hours per week. They were randomly assigned to middle school students, from a list of potential beneficiaries compiled by school principals. Using original survey data collected from students, parents, teachers and tutors, we find that the program substantially increased students' academic performance (by 0.26 SD on average) and that it significantly improved their socio-emotional skills, aspirations, and psychological well-being. Effects are stronger for children from lower socioeconomic status and, in the case of psychological well-being, for immigrant children.
Keywords: I24; I21; 330; tutoring; COVID-19; education; achievement; aspirations; socioemotional skills; well-being